Where there is hope: a qualitative study examining patients' adherence to multi-drug resistant tuberculosis treatment in Karakalpakstan, Uzbekistan. Issue 1 (December 2016) - Horter, Shona; Stringer, Beverley; Greig, Jane; Amangeldiev, Akhmet; Tillashaikhov, Mirzagaleb; Parpieva, Nargiza; Tigay, Zinaida; du Cros, Philipp
Abstract Background Treatment for multi-drug resistant tuberculosis (MDR-TB) is lengthy, has severe side effects, and raises adherence challenges. In the Médecins Sans Frontières (MSF) and Ministry of Health (MoH) programme in Karakalpakstan, Uzbekistan, a region with a high burden of MDR-TB, patient loss from treatment (LFT) remains high despite adherence support strategies. While certain factors associated with LFT have been identified, there is limited understanding of why some patients are able to adhere to treatment while others are not. We conducted a qualitative study to explore patients' experiences with MDR-TB treatment, with the aim of providing insight into the barriers and enablers to treatment-taking to inform future strategies of adherence support. Methods Participants were purposively selected. Programme data were analysed to enable stratification of patients by adherence category, gender, and age. 52 in-depth interviews were conducted with MDR-TB patients (n  = 35) and health practitioners (n  = 12; MSF and MoH doctors, nurses, and counsellors), including five follow-up interviews. Interview notes, then transcripts, were analysed using coding to identify emerging patterns and themes. Manual analysis drew upon principles of grounded theory with constant comparison of codes and categories within and between cases to actively seek discrepancies and generate concepts from participant accounts. Ethics approval was received from the MoH of the Republic of Uzbekistan Ethics Committee and MSF Ethics Review Board. Results Several factors influenced adherence. Hope and high quality knowledge supported adherence; autonomy and control enabled optimal engagement with treatment-taking; and perceptions of the body, self, treatment, and disease influenced drug tolerance. As far as we are aware, the influence of patient autonomy and control on MDR-TB treatment-taking has not previously been described. In particular, the autonomy of married women around treatment-taking was potentially undermined through their societal position as daughter-in-law, compromising their ability to adhere to treatment. Patients' engagement with and adherence to treatment could be hindered by hierarchical practitioner-patient relationships that displaced authority, ownership, and responsibility from the patient. Conclusions Our findings reinforce the need for an individualised and holistic approach to adherence support with engagement of patients as active participants in their care who feel ownership and responsibility for their treatment.